Hacia una expectante significación de las acciones humanas en Jóvenes Agrópolis (2008)
The interest to shape in the reality the scientific studies proposed from the investigation project Discursos de la acción humana en la Psicología (Speeches of the Human Action in Psychology) and in the interest to generate from this project a proposal to the institutional project Jóvenes Agrópolis (Agropolis youngsters) that make educational of the Field Psychology of the Relations, Networks and Narratives of the University Santo Tomás, It take to visualize the necessity to generate a strategy that allowed to include/understand youth from their human reality and not from the prejudices and the labels to which science and the society have had it put under. This article presents the antecedents that gave rise to the IASA (Instrument of Analysis for the Meaning of the Human Actions) propose methodology for the understanding a youth like the one of young people "agrópolis" Keywords: Youth, Meaning, Sense, Human action.